Адаптивный метод повышения помехозащищенности систем зондирования атмосферы - Рыбников, Н. В.; Капуста, А. И.; Нестеров, М. А. (My University, 2020)
The report shows that when constructing signal processing algorithms in sodars equipped with phased antenna arrays, it is advisable not only to form the distribution of zeros of radiation patterns in the directions to the sources of interference, but also to choose the radiation angles of the useful signal in order to minimize the interference power at the output of the array. The procedure for generating the interference power function at the output of the acoustic antenna array consists in forming the correlation matrix of the interference, its subsequent circulation, and the formation of the spatial spectrum of external acoustic interference on this basis. The directions of sounding the atmosphere will correspond with the directions in which the minimum values of the interference power at the output of the antenna array are observed.
Keywords: зондирование атмосферы; повышение помехозащищенности